Medieval features and finds from Balfarg/Balbirnie, Fife (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports shallow pits and a possible mill-lade found whilst excavating an earlier site. There are details of: `The pottery' by Derek W Hall (1011--13); `Metal, glass, coins and jet' by Barbara A Ford (1014--15); `Coins' by Nicholas McQ Holmes (1015--16); and `Documentary sources' by Catriona M M Graham (1016).